Never panic early : an Apollo 13 astronaut's journey - Haise, Fred, 1933-; Moore, Bill (Billy Don) (Smithsonian Books, 2022)
"The extraordinary autobiography of astronaut Fred Haise, one of only 24 men to fly to the moon"--